PRINSIP KESANTUNAN DAN PRINSIP KERJA SAMA DALAM KOMUNIKASI DI ULASAN PRODUK PADA MARKETPLACE - Didik Suharijadi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
This article discusses how to apply principles of cooperation and principles of politeness in communication between sellers and buyers in online business. The research object is specialized in online business through the marketplace and more specifically on product reviews. Marketplace is a platform or online system that mediates transactions between sellers and buyers. Marketplace has the tools of communicating between seller and buyer consisting of product description page, product discussion page, product review page, and personal message page. Of the four communication facilities are only product description pages, product discussion pages and product reviews pages that can be accessed by the public. Private message pages can only be accessed by the account owner who is communicating with other account owners. Product reviews are an important facility as most potential buyers see product reviews before buying. Product descriptions and product discussions are also important to note, but more product reviews show evidence of the quality of product and services. The reality is that not all marketplace users look at the pragmatic principles of communicating in product reviews. Specializing in product reviews is also based on frequent conflicts in product reviews between the seller and the buyer at this communication facility. The sample of this research is Tokopedia marketplace. Samples are selected because that marketplace is one of the largest online business media in Indonesia.